Mn-Rich Nanostructures in Ge1-xMnx: Fabrication, Microstructure, and Magnetic Properties - Ying Jiang; Yong Wang (Advances in Materials Science and Engineering, 2012)
Magnetic semiconductors have attracted extensive attention due to their novel physical properties as well as the potential applications in future spintronics devices. Over the past decade, tremendous efforts have been made in the diluted magnetic semiconductors (DMS) system, with many controversies disentangled but many puzzles unsolved as well. Here in this paper, we summarize recent experimental results in the growth, microstructure and magnetic properties of Ge-based DMSs (mainly Ge1-xMnx), which have been comprehensively researched owing to their compatibility with Si microelectronics. Growth conditions of high-quality, defect-free, and magnetic Ge1-xMnx bulks, thin films, ordered arrays, quantum dots, and nanowires are discussed in detail.